2021
DOI: 10.1038/s41388-021-02015-w
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin potentiates the cytotoxic effect of Neratinib in HER2+ breast cancer through promoting endocytosis and lysosomal degradation of HER2

Abstract: Complete blockade of the HER2 protein itself and HER signaling network is critical to achieving effective HER2-targeted therapies. Despite the success of HER2-targeted therapies, the diseases will relapse in a significant fraction of patients with HER2+ breast cancers. How to improve the therapeutic efficacy of existing HER2-targeted agents remains an unmet clinical need. Here, we uncover a role of Melatonin in diminishing HER2-mediated signaling by destruction of HER2 protein. Mechanistically, Melatonin treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 58 publications
(59 reference statements)
0
8
1
Order By: Relevance
“…As shown in Figure A, after being internalized by NCI-N87 cells, the colocalization phenomenon between the HApt-tFNA@Dxd and lysosomes was observed, which indicated that HApt-tFNA@Dxd might be degraded by lysosomes and then the Dxd was released. Meanwhile, the HER2 protein-mediated endocytosis of HApt-tFNA@Dxd would stimulate lysosomal degradation of HER2 protein. Therefore, Western blotting was conducted to test the changes of the HER2 protein. After treating the NCI-N87 cells with different DNA nanoparticles, the HER2 protein content decreased significantly in the HApt-tFNA- and HApt-tFNA@Dxd-treated groups compared to other groups (Figure S10A,B, Supporting Information), which further reflected the excellent HER2 targeting and mediating HER2 lysosomal degradation of HApt-tFNA and HApt-tFNA@Dxd.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure A, after being internalized by NCI-N87 cells, the colocalization phenomenon between the HApt-tFNA@Dxd and lysosomes was observed, which indicated that HApt-tFNA@Dxd might be degraded by lysosomes and then the Dxd was released. Meanwhile, the HER2 protein-mediated endocytosis of HApt-tFNA@Dxd would stimulate lysosomal degradation of HER2 protein. Therefore, Western blotting was conducted to test the changes of the HER2 protein. After treating the NCI-N87 cells with different DNA nanoparticles, the HER2 protein content decreased significantly in the HApt-tFNA- and HApt-tFNA@Dxd-treated groups compared to other groups (Figure S10A,B, Supporting Information), which further reflected the excellent HER2 targeting and mediating HER2 lysosomal degradation of HApt-tFNA and HApt-tFNA@Dxd.…”
Section: Resultsmentioning
confidence: 99%
“…Future in vivo experiments are needed to verify the above results. Additionally, melatonin synergizes with chemotherapy [ 8 , 39 , 40 ], and our experimental data indicated melatonin enhances the anti-proliferative action of β-catenin or HDACs inhibitors on ESCC cells. Future research directions should include the practical applications of melatonin based on pre-clinical and clinical studies, and determining in more detail and with more accuracy the molecular pharmacological mechanisms of melatonin in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…found in HFD-induced Obesity (72). It is reported that the treatment of melatonin significantly reduces the mRNA expression of PTGS2 (73).…”
Section: Details Of Top 10 Melatonin Targets In Treating Obesitymentioning
confidence: 96%